Conditions of School Buildings in India An Empirical Study - Singh, Virendra Pratap (JOURNAL OF INDIAN EDUCATION, 2013)
The present study empirically examines the conditions of school buildings pertaining to the types of school buildings, ownership of school premises, additional classrooms required and rooms used for instructional purposes. This paper utilises the secondary data collected during the recent successive two, namely, sixth and seventh surveys on school education conducted by the National Council of Educational Research and Training (NCERT) under administrative and financial control of Government of India (GOI). In totality, the findings of this study reveal that proper public regulations are required for accommodating all children in school buildings irrespective of management, and implementation thereof in practice.